Study on synthetic evaluation of lakes water quality improvement policies in Wuhan City in China - Xuebo Zhan; Jingjing Yan; Yoshiro Higano; Huanzheng Du (European Regional Science Association (ERSA), 2010)
Wuhan City is located in the central part of China, which is an import foothold of the transportation, manufacturing industry, commerce and education in China. Chinese government appointed Wuhan City as a national pilot reform area of resource-saving and environmentally friendly society at the end of 2007. There is a great deal of fresh water resources in Wuhan City, and Wuhan City is known as 'the city with 100 lakes'. However, about 60% of the lake water resources have became seriously polluted in Wuhan City. The most important reason for water degradation of Wuhan City is the imbalance between rapid economic development and the environment load capacity. In this study, we raised synthetic policies to reduce amount of lake water pollutants and realize the harmonious development between regional economy and water environment. In this paper, we focused on three contamination materials (COD, T-N and T-P) and constructed a model from environmental load, socio-economy and water quality improvement policies. We performed optimization simulation based on linear programming to maximize gross regional production (GRP) and reduce environmental load, and finally we suggested proper policies to improve water quality in this area.
Keywords: 330; Environmental policy; lakes water quality improvement; Modeling; Simulation